EDUCATIONAL TECHNOLOGIES IN TRAINING OF CHEMICAL PROCESS ENGINEERS - Farida T. Shageeva; Vasily G. Ivanov (Высшее образование в России, 2016)
Technification of educational process is a stable development trend for institutions of higher education. Exemplified by the course “General chemical engineering”, implementation of modular and context educational technology is shown. The course is included into the chemical process engineering curriculum. Modular and context technologies ensure development of engineering thinking of a future professional.